2014
DOI: 10.1016/j.ajpath.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Rtp801 Suppression of Epithelial mTORC1 Augments Endotoxin-Induced Lung Inflammation

Abstract: The mechanistic target of rapamycin (mTOR) is a central regulator of cellular responses to environmental stress. mTOR (and its primary complex mTORC1) is, therefore, ideally positioned to regulate lung inflammatory responses to an environmental insult, a function directly relevant to disease states such as the acute respiratory distress syndrome. Our previous work in cigarette smoke-induced emphysema identified a novel protective role of pulmonary mTORC1 signaling. However, studies of the impact of mTORC1 on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 22 publications
2
39
0
Order By: Relevance
“…This effect underscores the anti-inflammatory function of mTOR and supports its role in ameliorating lung inflammation [2]. The primary complex of mTOR mediates anti-inflammatory responses in the lung [2].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…This effect underscores the anti-inflammatory function of mTOR and supports its role in ameliorating lung inflammation [2]. The primary complex of mTOR mediates anti-inflammatory responses in the lung [2].…”
Section: Introductionmentioning
confidence: 72%
“…This effect underscores the anti-inflammatory function of mTOR and supports its role in ameliorating lung inflammation [2]. The primary complex of mTOR mediates anti-inflammatory responses in the lung [2]. Sirolimus has also been shown to induce severe immunosuppression in mice, as a result of thymus involution due to cortical lymphocyte apoptosis [3].…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, the individual expression levels of inflammation-associated genes may also influence the subsequent response to mTOR inhibitors. For example, in mice that are deficient for Rtp801, which is a negative regulator of mTORC1, rapamycin strongly enhances LPS-induced lung inflammation [39]. Interestingly, environmental cues such as cigarette smoke promote activation of Rtp801 [37].…”
Section: Discussionmentioning
confidence: 98%
“…Recently, it has been shown that activation of mTOR inhibits inflammatory responses and apoptosis in the lung of mice due to cigarette smoke or LPS [37][38][39]. Therefore, we speculated that inhibition of mTOR in the innate immune system might exaggerate an initial insult in the lung leading to augmented inflammatory responses and lung damage that may be at the base of DIP.…”
Section: Introductionmentioning
confidence: 92%
“…We created Rtp801-overexpressing mice (Tg-TRE-RTP801) (20). TgRtp801 MLF were purified and cultured as described above.…”
Section: Rtp801 Overexpression In Mlfmentioning
confidence: 99%